Insights into CO oxidation on Au/TiO2-HMor zeolite catalysts at low temperature - Camposeco, R.; Sánchez-Flores, N. A.; Zanella, R. (Frontiers in Nanotechnology, 2024)
The effect of combining TiO2 and mordenite zeolite (HMOR), employed as support of gold nanoparticles, on the CO oxidation reaction at low temperature is studied. The amount of TiO2 encapsulated into HMOR was varied and the catalyst efficiency was investigated. The deposition-precipitation with urea (DPU) method was used to deposit gold nanoparticles; likewise, the synthesis of monometallic catalysts based on TiO2 and HMOR is reported. The synthesized materials were characterized by X-ray diffraction (XRD), nitrogen adsorption, X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared spectroscopy (FTIR), and transmission electron microscopy (TEM). The addition of TiO2 influenced the properties of the TiO2-HMOR composite, and its catalytic performance in the CO oxidation from 20°C. It was established that the 5Au/(28)TiO2-HMOR composite was the most active catalyst at lower temperatures, which was ascribed to the close contact among the components of the TiO2-HMOR composite, gold dispersion, gold and TiO2 loadings, and Au and Ti species present in the catalysts.